KOMITMEN ORGANISASI DAN ASIMETRI INFORMASI SEBAGAI PEMODERASI PENGARUH KEJELASAN SASARAN ANGGARAN PADA SENJANGAN ANGGARAN - Wiguna, I Wayan Adi; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This study aimed to examine the effect of budget goal clarity on budgetary slack and to determining the commitment of organization and the information asymmetry in moderating influence budget goal clarity on budgetary slack in the regional government of Badung regency, research on 36 SKPD Badung. Sample selection is done by using purposive sampling method. Total respondents 108 people consisting of 36 Chief SKPD, 36 Head of Sub Division of General and Planning and 36 Head of sub-section of Finance. Data collected through questionnaires. The analysis technique used in this study is Moderated Regression Analysis. The study found that the budget goal clarity negative influence on budgetary slack, commitment organizational strengthening the influence of budget goal clarity on budgetary slack, and information asymmetry weaken the influence of budget goal clarity on budgetary slack.
Keywords: budgetary slack, budget goal clarity, organizational commitment, the asymmetry of information